Getting to the core: Internal body temperatures help reveal the ecological function and thermal implications of the lions' mane. Issue 1 (20th December 2016) - Trethowan, Paul; Fuller, Andrea; Haw, Anna; Hart, Tom; Markham, Andrew; Loveridge, Andrew; Hetem, Robyn; du Preez, Byron; Macdonald, David W.
Abstract: It has been proposed that there is a thermal cost of the mane to male lions, potentially leading to increased body surface temperatures ( T s ), increased sperm abnormalities, and to lower food intake during hot summer months. To test whether a mane imposes thermal costs on males, we measured core body temperature ( T b ) continuously for approximately 1 year in 18 free‐living lions. There was no difference in the 24‐hr maximum T b of males ( n  = 12) and females ( n  = 6), and males had a 24‐hr mean T b that was 0.2 ± 0.1°C lower than females after correcting for seasonal effects. Although feeding on a particular day increased 24‐hr mean and 24‐hr maximum T b, this phenomenon was true of both male and female lions, and females had higher 24‐hr mean and 24‐hr maximum T b than males, on both days when lions did not feed, and on days when lions did feed. Twenty‐four‐hour T b was not influenced by mane length or color, and 24‐hr mean T b was negatively correlated with mane length. These data contradict the suggestion that there exists a thermal cost to male lions in possessing a long dark mane, but do not preclude the possibility that males compensate for a mane with increased heat loss. The increased insulation caused by a mane does not necessarily have to impair heat loss by males, which in hot environments is primarily through respiratory evaporative cooling, nor does in necessarily lead to increased heat gain, as lions are nocturnal and seek shade during the day. The mane may even act as a heat shield by increasing insulation. However, dominant male lions frequent water points more than twice as often as females, raising the possibility that male lions are increasing water uptake to facilitate increased evaporative cooling. The question of whether male lions with manes compensate for a thermal cost to the mane remains unresolved, but male lions with access to water do not have higher T b than females or males with smaller manes. Abstract : Male lions with manes do not have higher internal body temperatures than females or males with shorter, lighter‐colored manes. These results contradict previous findings that the lions' mane is associated with a thermal cost. However, dominant male lions frequented water points more than females and nomadic males, possibly suggesting that male lions compensate for the thermal cost of the mane with increased evaporative heat loss.